PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. WISC INDONESIA - Annisa Islamiati; Dr. Ismail Razak, M.Si.; Puteri Herlanies Susanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The purpose of this study is to analyze the effect of career development and work motivation on the performance of employees of PT. WISC Indonesia. The data used are primary data through questionnaires to employees of PT. WISC Indonesia as respondent. The analytical method used is a simple and multiple linear regression analysis. The results indicated that career development and work motivation had a positive and significant effect on the performance of employees of PT. WISC Indonesia.